Effects of Storm Surges on the Beaufort Sea Coast, Northern Alaska - Reimnitz, Erk; Maurer, Douglas K. (ARCTIC, 1979)
In 1970, a major storm surge caused by gale-force westerly winds inundated low-lying tundra plains and deltas as far as 5000 m inland and left a driftwood line as much as 3.4 m above normal sea level along the Beaufort Sea coast of Alaska. The height of the surge followed a predictable pattern and was highest along windward-facing shorelines. Coastal retreat and thermoerosion are greatly accelerated on such west-facing shores with eastward sediment transport opposite to normal littoral drift. Evidence suggests an approximate 100-year recurrence interval for similar surges, with potential for damaging the developing oil fields on the North Slope.